The Tourism Observatory of Alentejo: a support instrument for foresight and strategic planning in the tourist sector in the region. - Figueira, Victor (2013)
It is the aim of this work to make a brief reference to the current situation of 'observatories' in Portugal as well as the change of their status, before developed through closed research circuits which included the Administration and Universities; nowadays characterized by the proliferation of more flexible and interactive structures very often as a result of private initiatives or public-private partnerships. We are also going to make a mention of two regional tourism observatories in Portugal - Lisbon and Azores - already established. Finally, it offers an overview of the new Tourism Observatory of Alentejo (presented in July 14th, 2010) as a result of a submission to an Incentive Scheme for Class Actions Program (SIAC) â€“ InAlentejo, which the main promoter is Alentejo Tourism, ERT, in partnership with the Polytechnics Institutes of Beja and Portalegre, the University of Ã‰vora and the regional business associations.